Exploring the Dolphy bakla: Queerness in Philippine cinema - Inton, Mikee N. (Animo Repository, 2018)
This chapter explores Philippine cinema’s representations of the bakla, a local gendered identitythat conflates ideas of male homosexuality and transgenderism. By examining the films of Dolphy, the chapter outlines tropes that have become associated with the bakla, including the conversion trope, where the bakla are forced to conform to traditional notions of masculinity. The chapter also identifies tensions between contemporary representations of the bakla as themasculine gay man and as the transgender woman in films – tensions that also exist within thewider Southeast Asian context. Looking at the bakla as the primary queer figure in Philippine cinema enables film audiences to examine more closely similar figures in other Asian cinemas: the kathoey of Thailand, the waria of Indonesia, and the mak-nyah of Malaysia